Rheological properties of mango (Mangifera indica l.) fruits in relation to handling and transport - Valerio, R. F.; Peralta, E. K.; Esguerra, E. B. (2001)
Compression, impact and vibration tests were conducted on 'Carabao' mango. Fruits at the green stage (peel color index 1 or PCI 1) withstood up to 80 kg of load with no significant internal damage. Compressive strength was reduced to 20 kg at the breaker stage (PCI 2) and 5 kg at 30% yellow peel color (PCI 3). This indicates that fruits should be transported immediately after harvest while their compressive strength is high. Cell rupture in the fruits occurred at 2.45 kN at PCI 1, at 0.63 kN at PCI 2, and at 0.50 kN at PCI 3. This implies that mango at the green stage can be stacked up to 5 layers using ordinary 20-kg capacity cartons. Stacking is not recommended for fruits at advanced stages of ripeness. The average impact coefficient across all drop heights ranged from 12.25 to 94.52 cm joule-1. This means that mango should never be dropped from a height greater than 0.26 m if the impact surface is carton, plastic or solid ground. Fruits in the top layers of crates subjected to simulated vibration were more susceptible to bruising than fruits in the bottom layers. A vibration intensity of 0.091g at 21,600 cycles (60 rpm for 6 h) resulted in bruising near the peel. Mangoes should therefore be properly cushioned during transport at high vibration intensity.
Keywords: Mango -- Quality control; Mango--Packaging.